Mouse galactokinase: isolation, characterization, and location on chromosome 11. - Ai, Y; Jenkins, N A; Copeland, N G; Gilbert, D H; Bergsma, D J; Stambolian, D

(untitled) (Genome Research, 1995)
Elevated galactose levels can be caused by several enzyme defects, one of which is galactokinase. Galactokinase deficiency cause congenital cataracts during infancy and presenile cataracts in the adult population. We have isolated the mouse cDNA for galactokinase, which shares extensive amino acid sequence homology, 88% identity, with a recently cloned human galactokinase. It is expressed in all tissues examined. In an interspecific backcross analysis galactokinase maps to the distal region of mouse chromosome 11, a region that is homologous to human chromosome 17q22-25. The availability of the mouse gene provides an opportunity to make a knockout model for galactokinase deficiency.